2007
DOI: 10.1117/12.758987
|View full text |Cite
|
Sign up to set email alerts
|

High sensitivity capacitive MEMS microphone with spring supported diaphragm

Abstract: Capacitive microphones (condenser microphones) work on a principle of variable capacitance and voltage by the movement of its electrically charged diaphragm and back plate in response to sound pressure. There has been considerable research carried out to increase the sensing performance of microphones while reducing their size to cater for various modern applications such as mobile communication and hearing aid devices. This paper reviews the development and current performance of several condenser MEMS microp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Weigold et al [13] was using a spring-supported, thin polysilicon diaphragm fabricated on silicon on insulator (SOI) wafer to achieve a sensitivity of -47 dB (ref 1 V/Pa) with the amplifier circuit. Another high sensitivity of up to 8.2 mV/Pa was reported by Fuldner et al [9] using a spring type diaphragm membrane of 1 mm in diameter and low bias voltage of 1 V. Mohamad et al [12,14] has also demonstrated that a specially designed spring-supported diaphragm can easily achieve up to 100 times higher mechanical sensitivity and 1.5 times higher capacitance change compared to the edge-clamped diaphragm of the same size.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Weigold et al [13] was using a spring-supported, thin polysilicon diaphragm fabricated on silicon on insulator (SOI) wafer to achieve a sensitivity of -47 dB (ref 1 V/Pa) with the amplifier circuit. Another high sensitivity of up to 8.2 mV/Pa was reported by Fuldner et al [9] using a spring type diaphragm membrane of 1 mm in diameter and low bias voltage of 1 V. Mohamad et al [12,14] has also demonstrated that a specially designed spring-supported diaphragm can easily achieve up to 100 times higher mechanical sensitivity and 1.5 times higher capacitance change compared to the edge-clamped diaphragm of the same size.…”
Section: Introductionmentioning
confidence: 86%
“…Since many small size audio applications prefer a low voltage operation, the microphone sensitivity needs to be increased by reducing the diaphragm stiffness alone. The diaphragm stiffness can be reduced by using a low stress material, perforated diaphragm or as a combination with corrugated or spring type diaphragm [4,[6][7][8][9][10][11][12]. However, the reduction in diaphragm stiffness will cause the reduction in its operating frequency range and pull-in voltage.…”
Section: Introductionmentioning
confidence: 99%
“…In one approach the material, including silicon nitride, polysilicon, aluminum, and polyimide (Scheeper et al 1991;Torkkeli et al 2000;Pedersen et al 1997;, and fabrication process of the diaphragm is optimized to increase the sensitivity while in the other, the structure is redesigned to obtain the same goal. The main problem in all mentioned structures (Ying et al 1998;Li et al 2001; Mohamad et al 2008;Kim et al 2006;Yang 2010), is that by an increase in the mechanical sensitivity the pull-in voltage significantly decreased, especially in spring supported diaphragm. In this paper a novel structure for diaphragm is proposed which can increase both mechanical sensitivity and effective area with no negative effect on pull-in voltage.…”
Section: Diaphragm Modelmentioning
confidence: 98%
“…In comparison to the normal diaphragms, the corrugated diaphragm has larger effective area, after the deflection, as well as higher mechanical sensitivity. Mohamad et al (2008) and Kim et al (2006), tried to increase both the mechanical sensitivity and the effective area, using some spring structures in their designs.…”
mentioning
confidence: 99%
“…Several designs of high sensitivity capacitive microphones have been demonstrated including corrugated, low-stress polysilicon, and spring supported based diaphragm [2][3][4][5][6][7] . However, the current analytical analysis is based on assumption that the small diaphragm movement is flat and piston-like to ease the microphone modeling and calculation involved 8, 9 . This paper highlights the non-flat deflection of a microphone diaphragm and demonstrates its effects on several types of microphone designs.…”
Section: Introductionmentioning
confidence: 99%